2021
DOI: 10.1186/s41687-021-00365-3
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-reported outcome measures in the care of in-centre hemodialysis patients

Abstract: Kidney failure requiring dialysis is associated with high symptom burden and low health-related quality of life (HRQL). Patient-reported outcome measures (PROMs) are standardized instruments that capture patients’ symptom burden, level of functioning, and HRQL. The routine use of PROMs can be used to monitor aspects of patients’ health that may otherwise be overlooked, inform care planning, and facilitate the introduction of treatments. Incorporating PROMs into clinical practice is an appropriate strategy to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[14][15][16]18,19 Patients and clinicians first alerted us to this need: We identified that mental health symptoms experienced by Canadians receiving dialysis are not routinely assessed and inadequately addressed. 6,[20][21][22][23][24] This was confirmed in our realist synthesis on patient-reported outcome use in kidney care [25][26][27] and by some of our community advisors in a kidney patient-led Patient and Community Engagement Research (PaCER) study on mental wellness 28 who wrote, "the most glaring gap in care is the lack of psychosocial support available to patients" (p. 3). However, the perspectives of people receiving dialysis regarding mental health supports have rarely been addressed.…”
Section: Introductionmentioning
confidence: 61%
“…[14][15][16]18,19 Patients and clinicians first alerted us to this need: We identified that mental health symptoms experienced by Canadians receiving dialysis are not routinely assessed and inadequately addressed. 6,[20][21][22][23][24] This was confirmed in our realist synthesis on patient-reported outcome use in kidney care [25][26][27] and by some of our community advisors in a kidney patient-led Patient and Community Engagement Research (PaCER) study on mental wellness 28 who wrote, "the most glaring gap in care is the lack of psychosocial support available to patients" (p. 3). However, the perspectives of people receiving dialysis regarding mental health supports have rarely been addressed.…”
Section: Introductionmentioning
confidence: 61%
“…This qualitative study was embedded within a pragmatic, cluster randomized controlled trial, Evaluation of routinely Measured PATient reported outcomes in HemodialYsis Care ( EMPATHY ) described elsewhere [ 25 ]. The initiative rolled out across 3 geographic areas in Canada and assessed the impact of bi-monthly screening of patients using PROMs paired with treatment guides (i.e., clinician- and patient-specific resources and handouts with suggested management approaches) on patient-clinician communication, clinical outcomes, and healthcare utilization compared with usual care [ 24 ]. This qualitative study took place across the 7 participating hemodialysis units assigned to an intervention group, where patients completed the Integrated Palliative Outcome Score [IPOS]-Renal, EQ-5D-5L, or both depending on unit allocation [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas comprehensive clinics that engage nursing, medical, and allied health professionals have become commonplace for individuals with advanced, non-dialysis-dependent chronic kidney disease [ 21 23 ], how care is integrated across disciplines and how tools such as PROMs might enable concerted care in the hemodialysis setting are not well understood. Alongside a program-wide initiative integrating PROMs into routine hemodialysis care across Southern Alberta, Canada [ 24 ], this study aimed to explore patients’ and clinicians’ perspectives on the role of PROMs in supporting interdisciplinary symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Each cluster (i.e., in-center hemodialysis unit) was randomized to one of four study arms: (1) patients complete the Edmonton Symptom Assessment System, Revised: Renal (ESAS-r: Renal) ( 24), (2) patients complete EQ-5D-5L ( 25), (3) patients complete both ESAS-r: Renal and EQ-5D-5L, and (4) usual care (i.e., control group). Nurses were trained on and delivered the intervention of routine PROM use (described in detail elsewhere) (23,26), which encompassed (1) self-reporting with allocated PROM(s) repeated every 2 months, (2) reviewing and discussing PROM(s) scores, and (3) using decision supports and patient handouts (27) to manage symptoms at the clinicians' discretion.…”
Section: Methodsmentioning
confidence: 99%
“…e ., control group). Nurses were trained on and delivered the intervention of routine PROM use (described in detail elsewhere) (23,26), which encompassed ( 1 ) self-reporting with allocated PROM(s) repeated every 2 months, ( 2 ) reviewing and discussing PROM(s) scores, and ( 3 ) using decision supports and patient handouts (27) to manage symptoms at the clinicians’ discretion.…”
Section: Methodsmentioning
confidence: 99%